Systematic significance of midrib vascular bundles in some Schefflera Spreng (Araliaceae) species - Aida Shafreena, Ahmad Puad; Noor Syaheera, Mohd Yunus; Noraini, Talip (AIP Publishing, 2014)
Anatomy study was undertaken on midrib vascular bundles of six Schefflera Spreng species, namely as S. obovatilimba, S. borneensis, S.kinabaluensis, S.lineamentorum, S. opacus and S.petiolosa. The genus Schefflera belongs to the family Araliaceae. The objective of this study is to determine variations in the midrib anatomical characteristics that can be used to identify species. Leaves samples were collected from various forest reserves in Sabah and Sarawak, Malaysia., were fixed in AA (Acetic acid: Alcohol, in a ratio of 1:3), the midrib parts then were sectioned using sliding microtome, were stained in Safranin and Alcian blue, been mounted in Eupharal and were observed under light microscope. Findings in this study have shown that all species have complex structure of vascular bundles. Each species has identical arrangement of vascular bundles and can be very useful for species identification. As a conclusion, variation in the midrib anatomical characteristics is outstanding and can has taxonomic value in the genus Schefflera respectively.